Comparison of Efficacy and Safety of Different Doses of Dexmedetomidine for Epidural Labor Analgesia - Liang Ge; Peng Zhang; Lingguo Kong; Wei Wang; Qian Tong; Quanlong Fan; Xudong Han (Emergency Medicine International)
Objective. To explore the efficacy and safety of different doses of dexmedetomidine (DEX) for epidural labor analgesia (ELA). Methods. From June 2021 to June 2022, 147 parturients who underwent ELA in our hospital were selected and divided into low- (0.5 μg/kg DEX), medium- (0.75 μg/kg DEX), and high-dose (1.0 μg/kg DEX) groups (n = 49 for each) according to the random number table method. The analgesic effect was assessed using the Ramsay sedation score and Visual Analogue Scale (VAS), and the labor duration, mean arterial pressure (MAP), and heart rate (HR) before and after analgesia, vaginal bleeding within 2 h postpartum, and delivery outcomes (the cesarean section conversion rate and the neonatal Apgar score) were statistically analyzed. Furthermore, the incidence of adverse reactions was calculated, and maternal satisfaction with delivery was investigated. Results. After analgesia, the the Ramsay and labor duration were higher in the high-dose group than those in the low- and medium-dose groups, and the VAS scores was lowerin the high-dose group than those in the low- and medium-dose groupsP<0.05, while no difference was identified among the three groups in terms of the cesarean section conversion rate and the neonatal Apgar score P>0.05. The high-dose group had the greatest fluctuations in MAP and HR levels before and after analgesia than the other two groups, with a higher incidence of adverse reactions P<0.05. Finally, the survey of delivery satisfaction showed no significant difference in delivery satisfaction among the three groups P>0.05. Conclusion. DEX has excellent performance in ELA, which can effectively relieve the pain of puerperae and shorten the labor process. Among them, low-dose DEX has higher safety and is recommended as the first choice. Trial Registrations. This trial is registered with ML2021073.